Tolak Ukur Pembebasan Pajak Bagi Lembaga Perkreditan Desa (LPD) Di Wilayah Provinsi Bali - I Wayan Bandem; I Nyoman Suandika (Jurnal Ilmiah Raad Kertha, 2019)
As Article 1 paragraph (3) of the State Constitution of the Republic of Indonesia is the stateof Indonesia is a state of law. Understanding the rule of law is simply a country whose administrationof power is based on law. and Article 1 paragraph (1) of the 1945 Constitution that the Indonesian stateis a Republican unitary state with a government structure that is the Government, Provincial RegionalGovernment, Regency / City Regional Government and the lowest government is the VillageGovernment which has their respective leaders based on legislation applicable legislation. Inconnection with the establishment of the LPD in article 33 of the 1945 Constitution and in Article 18Bparagraph (2) of the 1945 Constitution of the Republic of Indonesia which reads "that the staterecognizes and respects customary law units and their traditional rights insofar as it is still alive andin accordance with the development of society and the principle of the unitary State of the Republic ofIndonesia, which is regulated in law. So the provincial government of Bali based on the Rural CreditSeminar dated February 21, 1984 in Semarang The Governor of Bali initiated the establishment ofVillage Heritage Institutions (LPD) in the province of Bali in the role of national development with theaim of: 1) Encouraging economic development in rural communities through targeted savings andeffective capital distribution; 2) Eradicating the practice of bondage, illegal pawns, and others in thecountryside; 3) Creating business opportunities for villagers and rural workers, and; 4) Increasingpurchasing power and facilitating traffic payments and circulation So that the authors are interested inexamining the Tax Exemption Benchmark for LPDs in Bali Province with the research method used isjuridical-normative research. Taking into account that the starting point of research on legislation andthe fact that it began from the founding of the LPD in 1984 until now has not been taxed. In the courseof its operation the LPD in Bali by the three Ministers in 2009 issued a Joint Decree of the Minister ofFinance, Minister of Home Affairs, Minister of State for Koprasi and Small and Medium Enterprisesand Governor of Bank Indonesia Number.351.1 / KMK.010 / 2009, Number 900-639A in 2009, Number01 / SKB / M.KUKM / IX / 2009, Number 11 / 43A / KRP.GBI / 2009 concerning the DevelopmentStrategy of Microfinance Institutions. Affirmed through a letter from the Minister of Home AffairsNumber 412.2 / 3883 / SJ dated November 4, 2009 to the managers of institutions microfinance thatdoes not yet have a clear institutional status based on the prevailing laws and regulations. So that theGovernor of Bali Made Mangku Pastika on behalf of the provincial government of Bali submits a Letterof Governor of Bali Number 900/8999 / PLP. Ekbang dated 15 December 2009 to Minister of InternalAffairs The Republic of Indonesia prihal; The Strategy for the Development of MicrofinanceInstitutions. Thus, with the issuance of Law Number 1 of 2013 concerning Microfinance Institutions(MFIs), it was stated that the Village Credit Institutions and Pitih Negari Granaries and institutionsthat existed before the Laws were in effect were declared to be based on adat and not subject to thisLaw. The real benefits of the existence of LPD can be proven by the distribution of net profits each yearas profit retribution by dividing the following: 60% for fertilizing LPD business capital, 10%production services for labor, contributions to Indigenous Villages 20% for development funds inPakraman Village, as well as 5% for social funds, and 5% for empowerment funds deposited by theLPD at the agency / agency that is given the authority to regulate and manage them based on the Perdaand Decree of the Governor of Bali.